Analysis of predominant factors for the occurrence of aviation incidents in Brazil - Araujo, Gabriel Joaquim Lima; Fortes, Giovanna Sepulveda de Oliveira Macedo; Oliveira, Victória Gomes Lourenço de; Moura, Italo Emmanoel Mesquita Oliveira de (Brazilian Journal of Production Engineering, 2025)
Context: Safety in Brazilian civil aviation is vital for the sector trust. The Brazilian Aeronautical Accidents Investigation and Prevention Center (CENIPA) investigates occurrences, classifying their causes into operational, human, and material factors. Objective: To identify the predominant factor in aeronautical incidents in Brazil (2014-2023), providing input to CENIPA to focus on preventive actions and increase the reliability of air operations. Method: Statistical quality control and the Pareto principle were used to identify trends, prioritize problems, and analyze the predominance of each factor. Results: It was concluded that CENIPA faces difficulties in identifying the causes of aeronautical incidents, as many factors were classified as unavailable in the database. The analysis of existing data reveals the predominance of the operational factor in incidents, accounting for approximately 96% of occurrences, with the human factor representing about 4%, and material and other factors showing almost negligible influence. The main types of occurrences associated with the operational factor were bird strikes and system/component failure or malfunction. Conclusions: It is recommended that CENIPA prioritize the development and implementation of solutions targeting the operational factor to reduce incidents in Brazilian civil aviation.